Jesuit survival and restoration : a global history, 1773-1900 - Maryks, Robert A.; Wright, Jonathan, 1969- (Studies in the history of Christian traditions ;, 2014)
Jesuit Survival and Restoration offers a global account of the Society of Jesus's history during the post-Suppression and post-Restoration eras.